Diagnostic Accuracy of Pyuria in Detection of Pediatric Urinary Tract Infections - Muhammad Sufyan; Pracha, Hafiza Saima; Iftikhar, Kiran; Mansoor, Khola Binet; Muhammad Ashfaq; Zaeem, Ahmad (Indus Journal of Bioscience Research, 2025)
Introduction: Urinary tract infection (UTI), a common childhood bacterial infection, presents with nonspecific symptoms like fever, vomiting, irritability, and abdominal pain. Early diagnosis is crucial to prevent complications. Pyuria as a marker for UTI varies in diagnostic accuracy based on urine concentration. This study assesses pyuria’s diagnostic accuracy in detecting pediatric UTIs, using urine culture as the gold standard across varied urine concentration groups. Methodology: This study at Mayo Hospital Lahore from January 23, 2025 to May 23, 2025 enrolled 190 children aged 2–12 suspected of UTI. Urine was sampled using midstream catch or Foley catheter. Urinalysis and culture were done for all samples, categorizing based on gravity and adjusting pyuria thresholds. Diagnostic measures were calculated for sensitivity, specificity, PPV, NPV, and overall accuracy. Results: Among 190 children (53.7% male, 46.3% female; mean age 7.29±3.22 years), fever was the most common symptom (62.1%). Urine culture was positive in 56.8% cases, with pyuria also positive in 56.3%. Pyuria had 87.1% sensitivity, 84.1% specificity, 87.8% PPV, 83.1% NPV, and overall accuracy of 85.7% compared to urine culture. Pyuria showed better performance in males and older children (7–12 years). Conclusion: Pyuria, adjusted for urine concentration, is highly accurate in detecting pediatric urinary tract infections, making it a useful initial screening tool. Nonetheless, urine culture confirmation remains crucial for accurate diagnosis and proper management.